Simplifying
2x + -1y + -3z = 5
Solving
2x + -1y + -3z = 5
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add 'y' to each side of the equation.
2x + -1y + y + -3z = 5 + y
Combine like terms: -1y + y = 0
2x + 0 + -3z = 5 + y
2x + -3z = 5 + y
Add '3z' to each side of the equation.
2x + -3z + 3z = 5 + y + 3z
Combine like terms: -3z + 3z = 0
2x + 0 = 5 + y + 3z
2x = 5 + y + 3z
Divide each side by '2'.
x = 2.5 + 0.5y + 1.5z
Simplifying
x = 2.5 + 0.5y + 1.5z